ANALYSIS OF DIFFICULTIES IN LEARNING TO READ FOR CHILDREN WITH SPECIAL NEEDS IN PRIMARY SCHOOL - Marcelinus Widananta; Sri Mardiyanti (Universitas PGRI Semarang, 2023)
Overcoming reading problems include physical and psychological disorders such as language, oral or written disorders, as well as mild motor problems and emotional disorders. Children with learning difficulties, such as dyslexia, face challenges in inclusive schools, requiring special attention in processing information, especially in reading. The reading process plays a key role in understanding issues and expanding students' knowledge. This research uses a qualitative approach with descriptive methods. The descriptive method in qualitative research aims to explain or describe facts, data and research objects systematically, following the natural context of the situation being observed. Data collection techniques include interviews, observation and documentation. Data analysis was carried out qualitatively by applying the Milles & Huberman analysis model. To ensure data validity, triangulation techniques were used to increase data reliability as well as references from relevant sources. Research results show that learning difficulties, such as dyslexia, affect students across a wide range of academic subjects. Reading skills have an important role in the student learning process, and teaching strategies must be adapted to individual student needs. Children with special needs need holistic support from family, school and technology to overcome their learning difficulties. With a deep understanding of the difficulties in learning to read for children with special needs, effective and sustainable learning strategies can be designed to provide adequate support and improve the quality of inclusive education.